A nationalist theory of secession - Maguire, R (2022)
In this thesis I argue that nations can have a right to unilaterally secede from a legitimate, non-usurping state. In addition, I argue that they are special in this regard. I argue that there is a presumption in favour of collective autonomy by nations, establishing this claim by showing that co-nationality can be an intrinsically valuable relationship and that this grounds a strong claim to self-determination. I then argue that there are no considerations that always defeat the presumption in favour of collective autonomy by nations—for example, unilateral secession from a legitimate state need not wrong citizens of the remainder state by wrongfully taking territory. As such, nations can have an undefeated claim right to unilaterally secede from a legitimate state.